2016
DOI: 10.32674/jis.v6i1.569
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Contribute to the Adjustment of International Students

Abstract: Leaving home to attend college is an important milestone for college students. However, the transition from home to college can be challenging, especially for students studying abroad. In this article, the authors explore factors that contribute to the academic, cultural, social, and psychological adjustments of international students. Adjustment issues include psychological distress such as homesick, depression, and anxiety. This article seeks to increase the reader’s understanding of some of the issues faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 40 publications
8
126
0
17
Order By: Relevance
“…Therefore, students must understand the importance of adjustment and its related factors (Misra et al, 2003). In this respect, Mesidor and Sly (2016) indicated that the level of self-efficacy among international students was significantly related to students' psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, students must understand the importance of adjustment and its related factors (Misra et al, 2003). In this respect, Mesidor and Sly (2016) indicated that the level of self-efficacy among international students was significantly related to students' psychological adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…The term "psychological flexibility" covers many meanings, like adapting to situational demands, re-configuring mental resources, shifting perspectives, and balancing competing desires, needs, and life domains (Kashdan and Rottenberg, 2010, p. 865). Various facets of flexibility have been studied; however, it is believed that (a) psychological inflexibility and negative emotions correlate positively (Fresco et al, 2006;Tavakoli et al, 2019), (b) anxiety and depression are related to the loss of flexibility (Kashdan and Rottenberg, 2010) and are likely to appear when people need to adjust to changes in their environment (Mitchell et al, 2007;Mitchell et al, 2007;Mesidor and Sly, 2016) while coping flexibility leads to lower anxiety and depression (Cheng and Cheung, 2005), and (c) psychological flexibility has a major contribution to well-being (Kashdan and Rottenberg, 2010;Wersebe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also indicated that personality characteristics affect the degree to which students integrate into their new academic and social environment at university. Research into this relationship has almost exclusively been carried out using the Big Five personality characteristics (Hirai et al, 2015;Mesidor & Sly, 2016), and no studies so far have investigated how more narrow-bandwidth personality features, such as dependency and self-criticism are related to academic or social integration into the university environment.…”
Section: Academic and Social Integrationmentioning
confidence: 99%